Parents' Attitudes Toward COVID-19 Vaccination for School Children in Jordan - Abo Zaid, Ahlam; Mahmoud Suliman, Mohammad; ALBashtawy, Mohammed; Ta’an, Wafa'; Aljezawi, Mean; Abdalrahim, Asem; Alkhawaldeh, Abdullah (Nurse Media Journal of Nursing, 2023)
Background: Vaccination against COVID-19 is pivotal in curbing the spread of the virus among school children. However, there is a dearth of studies exploring parents’ attitudes and acceptance levels regarding immunizing their children against COVID-19 in Jordan.Purpose: This study aimed to assess parents’ attitudes and key concerns toward administering COVID-19 vaccines to their school-aged children in Jordan. Additionally, it sought to identify the differences in parents’ attitudes based on socio-demographic variables.Methods: The cross-sectional and correlational study was conducted in AL-Mafraq governance within Northeastern Badia schools from March to May 2022 and involved 498 eligible parents. Stratifying the parent population based on school districts, data were conveniently collected using the Parent Attitude about Childhood Vaccines (PACV) scale. Statistical Package for the Social Sciences (SPSS) version 17 facilitated data analysis, incorporating descriptive and inferential statistics at a significance level of 0.05, with a 5% margin of error. The independent t-test and One-Way ANOVA were employed to depict differences between studied variables.Results: The result showed that out of 600 distributed questionnaires, 498 were returned, resulting in a response rate of 83%. Findings revealed parental reluctance toward administering COVID-19 vaccination to their children. Notably, 65.9% of parents expressed concern about potential serious side effects, while 57.8% of parents harbored anxieties about vaccine safety and efficacy. Marital status emerged as a significant factor, with widowed parents exhibiting a more favorable attitude (p<0.05).Conclusion: Parents in Jordan are hesitant about COVID-19 vaccination for their school-aged children. Addressing these concerns necessitates educational campaigns through various channels, including social media and authorized TV and radio, to reassure parents about vaccine effectiveness and safety. This proactive approach is crucial to fostering broader acceptance and ensuring the success of vaccination initiatives.